Evaluation of influenza vaccination services in a community pharmacy in Lisbon, Portugal - Aguiar, J. P. (2015)
Poster presented at the 9th PCNE (Pharmaceutical Care Network Europe) Working Conference. Mechelen (Belgium), 2015